Soil Water Evaporation as Affected by the Placement of a Coarse Layer: a Laboratory Soil Column Study - ASSEED, MOHAMED (The Libyan Journal of Agriculture, 2023)
Wetted soil columns, which were packed with sandy loam soil, were subjected to a uniform daily evaporation potential. These soil columns were treated with the placement of coarse sand layers of different thicknesses, placed on the soil surface or 4 cm below the SOIL WATER EVAPORATION 89 soil surface. Evaporation with time, water redistribution after evaporation, and thickness of the dry surface layer were measured. It was found that evaporation is characterized by three stages, the initial constant high rate, the declining rate, and the final constant slow rate. In the first stage the evaporation rate approaches the evaporation potential, which indicates that when the soil is moist directly after irrigation, evaporation will approach openpan evaporation. The final constant slow rate for the soil studied was approximately equal to 0.1 cm/day, which gives an indication about the transmitting properites of this soil. When a layer of coarse sand was placed on the soil surface, the first stage rate was decreased but its duration was prolonged, depending on the thickness of the coarse sand layer placed on the soil surface. The appreciable reduction in evaporation loss at the end of an evaporation period = 25 days occurred when this coarse sand layer = 1 cm. The data indicates the importance of both time and rate of application of a coarse sand layer on soil surface in evaporation reduction. When a coarse sand layer of a different thickness wasplaced 4 cm, below soil surface, capillary discontinuity wasachieved. and evaporation loss was greatly reduced. This reduction was about 76% compared to the evaporation loss from bare soil. The difference in thickness of this coarse sand layer which was placed 4 cm below surface, did not result in much difference in evaporation loss reduction. The thickness of the dry surface layer was about 6 cm, and this is the vaporization zone. Moisture distribution after evaporation indicates that when a coarse sand layer was placed 4 cm below the soil surface, the moisture content of the soil just below this coarse sand layer did not change much from the initial moisture content. This ensures the impedence of capillary movement in the upward direction due to the presence of this coarse sand layer below the soil surface.